A Review on Methods of Synthesis of Quinazolines and (4H)-3,1-Quinazolin-4-ones - Darwish, K.; Dakhil, O. (Libyan Journal of Science &Technology, 2022)
The main objectives of organic and medicinal chemistry are the design, synthesis and production of molecules having valuable human therapeutic effects. There are numerous biologically active molecules with six-membered rings, containing two heteroatoms. The development of research on biological activity of quinazoline compounds started with the synthesis of 2-methyl-3-phenylquinazolin-4(3H)-one that was later on approved to have has soporific and sedative action. This biological importance encouraged scientists to develop various new synthetic pathways of novel products. This review may cover and explain most of the old and recent synthetic methods of quinazolines and quinazolinones over more than a century.